Economic aspects and business implications of widespread adoption of electronic commerce and transactions - Kopets, Galyna; Rachynska, Galyna; Dzyubina, Kateryna (Lviv Polytechnic Publishing House, 2016)
Organizations around the globe are facing the new type of challenges predominantly associated with adoption of electronic commerce and transactions and successful inclusion of this relatively new form of interaction into the existing business model. The process of embracing this change requires a number of alterations to organizational institutions and culture, decision making, as well as technological infrastructure.
Keywords: e-commerce; electronic commerce and transactions adoption; electronic transactions; innovation; change; organizational change; electronic transactions; growth strategies